Teokrasi dalam Kitab Daniel sebagai Rujukan Prinsip Ketaatan pada Keputusan Pemerintah Eksekutif - Nassa, Grace Son (KARDIA: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Abstract: This research aims to analyze and expose the theocracy in the book of Daniel, then use it as a reference for the principle of obedience to the executive government towards a decision on the proposed change in the nomenclature of Isa Almasih to Jesus Christ. Because there is very little or no research that links the theocracy of the book of Daniel with the issue of changing the nomenclature of Isa Almasih to Jesus Christ. The method used is content analysis. Thus, the book of Daniel will be analyzed, especially the theme of theocracy in it and then the pattern of theocracy will be constructed based on the findings. The pattern is then used as a principle of obedience to the government's decision regarding the proposed change in the nomenclature of Isa Almasih to Jesus Christ. As a result, the theocracy building constructed from the book of Daniel has effectiveness for His chosen people personally and communally, which has an apocalyptic dimension and is strongly tied to eschatological expectations. This cannot be separated from the Jewish tradition that is closely related to theocracy. This research can enrich the discourse on theocracy for Christians in particular through the perspective of the book of Daniel and can be used as a principle of obedience to the executive government's decision on a decision.   Abstrak: Penelitian ini bertujuan untuk menganalisis dan mengekspos teokrasi dalam kitab Daniel, lalu dijadikan sebagai rujukan prinsip ketaatan pada pemerintah eksekutif terhadap sebuah keputusan tentang usulan perubahan nomenklatur Isa Almasih menjadi Yesus Kristus. Sebab sangat sedikit bahkan belum ada penelitian yang mengaitkan teokrasi kitab Daniel dengan masalah perubahan nomenklatur Isa Almasih menjadi Yesus Kristus. Metode yang digunakan adalah analisis konten. Dengan demikian, kitab Daniel akan dianalisis khususnya tema teokrasi yang ada di dalamnya lalu dikonstruksi pola teokrasi berdasarkan hasil temuan tersebut. Pola itu kemudian dijadikan sebagai prinsip ketaatan pada keputusan pemerintah terkait usulan perubahan nomenklatur Isa Almasih menjadi Yesus Kristus. Hasilnya, bangunan teokrasi yang dikonstruksi dari kitab Daniel memiliki keefektifan bagi umat pilihan-Nya secara personal maupun komunal, yang memiliki dimensi apokaliptik dan terikat kuat dengan harapan eskatologis. Hal itu tidak lepas dari tradisi Yahudi yang berkait erat dengan teokrasi. Penelitian ini dapat memperkaya wacana tentang teokrasi bagi umat Kristen khususnya melalui perspektif kitab Daniel dan dapat dijadikan sebagai prinsip ketaatan terhadap keputusan pemerintah eksekutif tentang suatu keputusan